DENTAL EXTRACTION TECHNIQUE USING DIFFULTY - Sagung Agung Putri Dwiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
The difficulty in dental extraction can happen, because of cases such as the number of and form of dental base which abnormal hypersementosysts of dental base, ankilosyst, bone schlerosist, dental crown which fragile especially post endodontic treatment. To overcome case with such local difficulties, closed method or open extraction approach can be deployed.